Retrieval and reattachment of an elusive tooth fragment - Savita Sangwan; Shivani Mathur; Samir Dutta (Wolters Kluwer Medknow Publications, 2011)
Traumatic dental injuries of uncomplicated nature are a common finding and upper central incisors are the most commonly affected teeth. Sometimes, the fractured fragment or the tooth gets embedded in the surrounding soft tissues and is often missed. There are few case reports regarding the retrieval and reattachment of tooth fragment. This report presents the case of an 8-year-old girl who came with the chief complaint of pain, irritation, and tingling sensation in the lower lip since one year when her upper central incisors got fractured due to trauma along with lip laceration. A soft tissue radiograph of lower lip revealed the presence of fractured tooth fragment which was then surgically removed and reattached to one of the fractured incisors. The patient was found to be asymptomatic after the procedure. This report further highlights the importance of proper radiographic diagnosis along with clinical examination immediately after trauma in order to prevent any complications in future.